2004
DOI: 10.1007/s10038-004-0146-3
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of transcriptional factor E2F1 in papillary and anaplastic thyroid cancers

Abstract: Expression of genes in the Rb-E2F signaling pathway is controlled by E2F transcriptional factors originally defined as molecules that bind to the promoter of E2 adenovirus. The E2F gene family consists of six members and is designated E2F1-6. The Rb-E2F signaling pathway is among the main regulators of the cell cycle, hence its importance in differentiation and oncogenesis. We document here up-regulation of E2F1, but not other members of the E2F gene family, in 15 of 18 primary papillary thyroid cancers examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
6
18
1
2
Order By: Relevance
“…Every cancer-related defect in these pathways should result in p14 ARF upregulation. We found an upregulation of E2F1 in all tumour types which is consistent with others studies (Saiz et al, 2002;Onda et al, 2004), and we observed a link between E2F1 and p14 ARF expression in nontumoral thyroid tissue as well as in follicular adenomas and carcinomas. These results suggest the involvement of E2F1 in the p14 ARF upregulation in these tumours.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Every cancer-related defect in these pathways should result in p14 ARF upregulation. We found an upregulation of E2F1 in all tumour types which is consistent with others studies (Saiz et al, 2002;Onda et al, 2004), and we observed a link between E2F1 and p14 ARF expression in nontumoral thyroid tissue as well as in follicular adenomas and carcinomas. These results suggest the involvement of E2F1 in the p14 ARF upregulation in these tumours.…”
Section: Discussionsupporting
confidence: 93%
“…For this we determined first the mRNA expression levels of E2F1 in the same tumours. Consistent with others studies, E2F1 levels were upregulated in all tumour types (Onda et al, 2004). This upregulation was statistically significant in PTC (P ¼ 0.0001) ( (Bates et al, 1998).…”
Section: P14 Arf Regulation By E2f1 Is Lost In Papillary Carcinomassupporting
confidence: 91%
“…After 72 hours, cells were collected and extracted RNA with TRIzol (Invitrogen). 7 The expression of OEATC-1 was evaluated with SQ-PCR in the manner described above.…”
Section: Transfection Of Psec Oeatc-1 To the Kta2 Cell Line And Gene mentioning
confidence: 99%
“…The complex was transfected into arranged KTA2 and it was cultured up to 7 days. At the determined time points of days 0, 3, 5 and 7, cells were collected and RNA was extracted with TRIzol (Onda et al, 2004b). The exogenous expression of HBB was confirmed with both SQ-PCR and Q-PCR in the same manner as described previously.…”
Section: Construction Of Hbb Expression Vectormentioning
confidence: 99%
“…Q-PCR was carried with qPCR Mastermix for Syber Green I (Eurogenetec, Seraing, Belgium) and ABI 7700 (Applied Biosystems, Foster City, CA, USA) described previously (Onda et al, 2004b). Primers for Q-PCR of HBB were the same as those used in the SQ-PCR study.…”
Section: Quantitative Rt -Pcrmentioning
confidence: 99%